Numerical Solution of Partial Differential Equations for Heat Transfer in Composite Materials - Carlos Alberto Gonzalez; Juan Felipe Sanchez; Mariana González Silva (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This paper presents a numerical solution approach for solving partial differential equations (PDEs) that describe heat transfer in composite materials. Using finite element analysis (FEA), we analyze temperature distribution and thermal gradients within various composite configurations. The results demonstrate that our numerical solution approach accurately predicts temperature behavior, providing insights for materials engineering and design. This method is particularly useful for optimizing thermal properties in engineering applications involving multilayer materials.